The Transformation of Ijârah: from Fiqh to Syariah Banking Products - Hasanudin Hasanudin; Ainul Yaqin (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2019)
Ijârah begins from the concept of classical fiqh as a transaction that sustains the development of Islamic banking. The wide range of banking products produced from the concept of ijarah is the basis for developing the concept of jurisprudence from classical fiqh contact to banking products in the form of financing. These developments can be seen from a large number of banking products that use ijârah contracts, especially those related to services. This development lies in the merger of ijârah contracts with several other contracts such as wakalah. Another development that exists in the path to ijarah financing is seen from the foundation. In classical fiqh concept, ijârah is a product of fiqh ijtihad which is ẓanni or not binding. Every Muslim may practice the concept of jurisprudence from many scholars as ijtihad. However, in the financing of the surcharge, it is a combination of several contracts and is based on the DSN-MUI fatwa which is more binding for Islamic financial institutions on the recommendation of the Islamic banking law. (Ijârah yang berawal dari konsep fikih klasik merupakan salah satu transaksi yang menopang perkembangan perbankan syariah. Luasnya cakupan produk perbankan yang dihasilkan dari konsep ijarah menjadi dasar bagi pengembagan konsep ijârah dari kontak fikih klasik menuju produk perbankan dalam bentuk pembiayaan. Perkembangan tersebut dapat dilihat dari banyaknya produk perbankan yang menggunkaan akad ijârah terutama yang berkaitan dengan jasa. Perkembangan tersebut terletak dari penggabungan kontrak ijârah dengan beberapa kontrak yang lain seperti wakalah. Perkembangan lain yang ada pada ijârah ke pembiayaan ijarah adalah dilihat dari dasar pijakan. Dalam kensep fikih klasik, ijârah merupakan produk ijtihad fikih yang bersifat dzanni tidak mengikat. Setiap orang Islam boleh mengamalkan konsep ijârah dari ulama manapun yang bersifat ijtihad. Namun dalam pembiayaan ijârah selaian merupakan gabungan dari beberapa akad dan berpijak pada fatwa DSN-MUI yang lebih mengikat bagi lembaga keuangan syariah atas anjuran dari undang-undang perbankan syariah.